TESTING INDUCTIVE SENSOR FOR MEASURING THICKNESS OF TOP LAYERS - Paweł, PTAK (Trends in education, 2014)
Article presents results of research an inductive electromagnetic transducer, which allow detection and location of subsurface defects and their occurrence in examined top layers. Measurements were performed for the selected signal operation of inductive transducer choosing the frequency, sensitivity and accuracy. Accurate measurement of thickness of protective layer was determined by means of Fischer precision instruments.
Keywords: : inductive sensor; frequency selection; top layers.